Corpus callosum and cerebellar vermis size in very preterm infants: Relationship to long-term neurodevelopmental outcome - Po-Ming Wu; Hsin-I. Shih; Wen-Hao Yu; Li-Wen Chen; Lie-Chuan Wang; Chao-Ching Huang; Yi-Fang Tu (Elsevier, 2019)
Background: The neonatal changes of corpus callosum or cerebellar volume in preterm infants have been shown to link with abnormal mentality and motor disability in early childhood. This study aims to predict the long-term neurological outcomes by measuring these changes on neonatal brain ultrasound in preterm infants. Methods: Our cohort consisted of infants aged below 32 weeks' gestation with very low birth body weights who completed neuro-assessments at 5 years of age. Corpus callosum or cerebellar vermis were measured at 28-30 weeks and at 37-40 weeks gestational age in premature infants with cerebral palsy (CP), mental retardation (MR) and normal control premature infants. Results: There are 12 patients in MR group, 12 in CP group and 27 patients as controls for final analysis. There was no significant difference in other factors between study groups except lower gestational age (P = 0.043) in CP group. Respiratory distress syndrome was more common in MR group (P = 0.037) and cystic periventricular leukomalacia was more common in CP group (P < 0.001) than controls. After adjusting for sex and birth body weight, the MR group had smaller cerebellar vermis area at 37-40 gestational weeks (P = 0.002) than controls. They also reduced the growth of corpus callosum area (difference = −0.12 ± 0.16, P = 0.029) and cerebellar vermis area (difference = 1.10 ± 0.44, P = 0.020) from 28 to 30 gestational weeks to 37-40 gestational weeks compared with controls (difference = 0.03 ± 0.15, 1.92 ± 0.70, respectively). In contrast, the CP group had reduced the growth of corpus callosum body (difference = −0.02 ± 0.18, P = 0.034) compared with controls (difference = 0.03 ± 0.04). They subsequently had smaller body thickness of corpus callosum (0.10 ± 0.02, P = 0.015) at 37-40 gestational weeks than controls (0.14 ± 0.04). Conclusions: Serial monitoring corpus callosum and cerebellar vermis size in early life of very preterm babies may predict the motor or mentality neurological outcome at 5 years of age. Key Words: cerebellum, cerebral palsy, cranial ultrasound, mental retardation, preterm